2000
DOI: 10.1073/pnas.240471297
|View full text |Cite
|
Sign up to set email alerts
|

Illegitimate Cre-dependent chromosome rearrangements in transgenic mouse spermatids

Abstract: The bacteriophage P1 Cre͞loxP system has become a powerful tool for in vivo manipulation of the genomes of transgenic mice. Although in vitro studies have shown that Cre can catalyze recombination between cryptic ''pseudo-loxP'' sites in mammalian genomes, to date there have been no reports of loxP-site infidelity in transgenic animals. We produced lines of transgenic mice that use the mouse Protamine 1 (Prm1) gene promoter to express Cre recombinase in postmeiotic spermatids. All male founders and all Cre-bea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
209
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 307 publications
(228 citation statements)
references
References 43 publications
12
209
1
Order By: Relevance
“…More detailed analysis indicated that proliferating, rather than postmitotic, cells were vulnerable to the effects of Cre recombinase, as cryptic recombination events were only observed in mitotically-active cells (Loonstra et al, 2001). There have been two reports of overt pathology in cre-expressing transgenic mice, where high levels of Cre resulted in male infertility when expressed in postmeiotic spermatids (Schmidt et al, 2000) and hydrocephaly when expressed in neuronal progenitors (Forni et al, 2006). In the latter study, the genotoxic effects required the levels of Cre recombinase to reach a critical, high threshold in the cell nucleus, as had been reported previously in vitro (Baba et al, 2005).…”
Section: Effects Of Cre Recombinasementioning
confidence: 55%
“…More detailed analysis indicated that proliferating, rather than postmitotic, cells were vulnerable to the effects of Cre recombinase, as cryptic recombination events were only observed in mitotically-active cells (Loonstra et al, 2001). There have been two reports of overt pathology in cre-expressing transgenic mice, where high levels of Cre resulted in male infertility when expressed in postmeiotic spermatids (Schmidt et al, 2000) and hydrocephaly when expressed in neuronal progenitors (Forni et al, 2006). In the latter study, the genotoxic effects required the levels of Cre recombinase to reach a critical, high threshold in the cell nucleus, as had been reported previously in vitro (Baba et al, 2005).…”
Section: Effects Of Cre Recombinasementioning
confidence: 55%
“…For abbreviations, see Table 1. pathologic condition further, however, it is possible that overexpression of Cre could be deleterious to neurons, as Cre expression has been shown to be toxic to cells in culture and in transgenic mice (Schmidt et al, 2000;Loonstra et al, 2001). Gene ablation by using the Cre-loxP system requires that Cre expression is spatially and temporally restricted to the tissue of interest, especially if one is studying the effects of ablating genes whose expression is widespread.…”
Section: Resultsmentioning
confidence: 99%
“…Obviously, poor cre expression in germ line cells cannot be the (only) reason for low or absent transmission of rearrangements via the germ line. Third, Cre toxicity causes somatic phenotypes in tomato , which may pose a problem in gametes especially when expressed to high levels as shown in mammalian cells (Schmidt et al (2000); Loonstra et al (2001)). Selection against Cre containing gametes can explain low over-all transmission frequencies of deletions through the germ line, but Cre toxicity is not expected to differentiate between larger and smaller deletions.…”
Section: Why Do Larger Somatic Deletions Occur Less Frequently Than Smentioning
confidence: 99%